2014
DOI: 10.7589/2013-07-186
|View full text |Cite
|
Sign up to set email alerts
|

BASELINE CUTANEOUS BACTERIA OF FREE-LIVING NEW ZEALAND NATIVE FROGS (LEIOPELMA ARCHEYIANDLEIOPELMA HOCHSTETTERI) AND IMPLICATIONS FOR THEIR ROLE IN DEFENSE AGAINST THE AMPHIBIAN CHYTRID (BATRACHOCHYTRIUM DENDROBATIDIS)

Abstract: ABSTRACT:Knowledge of baseline cutaneous bacterial microbiota may be useful in interpreting diagnostic cultures from captive sick frogs and as part of quarantine or pretranslocation disease screening. Bacteria may also be an important part of innate immunity against chytridiomycosis, a fungal skin disease caused by Batrachochytrium dendrobatidis (Bd). In February 2009, 92 distinct bacterial isolates from the ventral skin of 64 apparently healthy Leiopelma archeyi and Leiopelma hochstetteri native frogs from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…There is a growing body of evidence that host skin microbiome communities affect host health. Several studies have shown that Bd- inhibiting skin bacteria from hosts can inhibit Bd growth and limit the effects of Bd on susceptible amphibians ( 36 , 80 , 86 , 87 ), and Bd inhibiting skin bacteria occur on many amphibian species ( 58 , 88 , 89 ), including terrestrial salamanders that live in California ( 90 , 91 ). In this study we found Bd inhibiting bacteria on both focal salamander species, with a high percentage of culturable species exhibiting Bd inhibition ( B. luciae , 100%; A. lugubris , 81.2%, and A. lugubris eggs, 75%) compared to other studies ( 58 , 89 , 92 , 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that host skin microbiome communities affect host health. Several studies have shown that Bd- inhibiting skin bacteria from hosts can inhibit Bd growth and limit the effects of Bd on susceptible amphibians ( 36 , 80 , 86 , 87 ), and Bd inhibiting skin bacteria occur on many amphibian species ( 58 , 88 , 89 ), including terrestrial salamanders that live in California ( 90 , 91 ). In this study we found Bd inhibiting bacteria on both focal salamander species, with a high percentage of culturable species exhibiting Bd inhibition ( B. luciae , 100%; A. lugubris , 81.2%, and A. lugubris eggs, 75%) compared to other studies ( 58 , 89 , 92 , 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…Frogs were swabbed (1 swab/frog) by running the natural fibre cotton tip across each of the following surfaces three times: dorsal (anterior to posterior), ventral (anterior to posterior), lateral (left and right sides), front legs from armpit to wrist (left and right sides) and back legs from groin to ankle (left and right sides) (adapted from Shaw et al [ 24 ] and Antwis et al [ 14 ] (Fig. 1 ).…”
Section: Bacteria Sample Collectionmentioning
confidence: 99%
“…During swab collection, frogs were removed from their individual containers and handled with separate sterile gloves (Skinshield powderfree latex gloves, Livingstone International, Rosebery, NSW, Australia) to prevent cross contamination of cutaneous bacteria [ 14,23 ]. Immediately prior to sampling, frogs were rinsed once with 30mL sterile water to remove transient bacteria [ 6,23,24 ], ensuring minimal handling to prevent loss of cutaneous bacteria.…”
Section: Bacteria Sample Collectionmentioning
confidence: 99%
“…The present study provides evidence that low nutrient R2A, relative to other common culture media, allows the growth of a higher diversity of bacterial taxa and recovers a higher proportion of the overall diversity occurring on the amphibian skin. These findings are relevant given that R2A has been widely used in the isolation of amphibian skin bacteria (e.g., Harris et al, 2006 ; Flechas et al, 2012 ; Daskin et al, 2014 ; Shaw et al, 2014 ; Antwis et al, 2015 ; Becker et al, 2015 ; Madison et al, 2017 ), despite no evidence of its proficiency. We suggest that an understanding of the ecological interactions influencing the plated communities and the nature of the culture media will likely improve our ability to culture rare or previously uncultured microbes.…”
Section: Discussionmentioning
confidence: 94%